Role and utility of the national registers of VATS major procedures - Divisi, Duilio; Zaccagna, Gino; Gabriele, Francesca; Crisci, Roberto (Video-Assisted Thoracic Surgery, 2017)
The national registers arise from the need to collect data in order to improve the known techniques and to direct towards new treatment strategies. In this study we tried to emphasize the importance of the sampling of information taking into account two aspects: (I) analysis of learning curves; (II) the choice of surgical strategies, by which to set a standardization of techniques designed to establish future treatment guidelines. Data collection and medical practice will influence each other. In fact, we find in literature several studies conducted on very large series which provide valuable support to the therapeutic choices. The goal is to reach new standards of treatment, through the consent of the national and international scientific community.